SPEECH, TEXT AND CONTEXT: ANALYSIS OF SPEECH AND LANGUAGES TEACHING IN THE COMPULSORY SCHOOLING - Belda Torrijos, Mónica (IJRDO - Journal of Social Science and Humanities Research, 2017)
The mastering of language is a necessary instrument to access the knowledge, for autonomous control of the sources and fields of science and knowledge. It also implies a necessary tool for the education of autonomous beings,who are capable of establishing and mastering the social and professional relations of their environment. In the last decades, we have witnessed a confluence between new language sciences (pragmatic, linguistic, discourse analysis) and new objectives entrusted to the area of language.Those no longer have as object of study the system of the language in use; communicative approaches of the teaching of languages insist on the need to develop not so much a knowledge about the language but a know-how with words. That is to say, there is a coincidence in which the object of study is not to be the code but the linguistic uses.